Regression model analysis for vessel service time - Mokhtar, Kasypi (2007)
Turnaround time in port industry portrays the capability and ability of a container terminal port in providing shipping services. This study is motivated by the rapid development in container terminal ports to provide efficient and effective services and high port productivity. The aim of this research is to develop mathematical relationships between port throughputs and port facilities. Presently, the factors that influence the performance of a port in terms of turnaround time are still debatable. This research proposes a regression model that relates the turnaround time and the port facilities. Two ports in Port Klang, i.e. the Westport and the Northport, were selected as the studied subjects from which the actual vessel call data were collected. A one - month data were used in the analysis. The overall results showed that the vessel turnaround time is highly correlated with crane allocation, number of containers loaded and discharged. The model relating these variables is in the form of multiple regression. The benefits of such a model include that of giving port operators the opportunity to determine optimum crane allocation in order to achieve the desired turnaround time given the quantity of containers to be processed.